A procedure to evaluate the efficiency of utilization of dietary amino acid for poultry - Silva, Edney Pereira Da [UNESP]; Sakomura, Nilva Kazue [UNESP]; Dorigam, Juliano Cesar De Paula [UNESP]; Malheiros, Euclides Braga [UNESP]; Fernandes, João Batista Kochenborger [UNESP]; Araujo, José Anchieta De [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2014)
The aim of this study was to develop a procedure based on Gompertz function to determine the efficiency of utilization of amino acid. The procedure was applied to determine the efficiency of utilization of dietary lysine, methionine+cystine and threonine by growing pullets and based on the efficiencies were estimated the requirements for the growth phase of birds. The Gompertz function was fitted to the data of feed intake, body weight, feather-free body protein weight and feather protein weight of four strains of laying hens in the growth phase. The rates of consumption and daily protein deposition (PD) were calculated. The amino acid deposition was obtained by multiplying the PD by the amino acid concentration in feather protein and feather-free body protein. The results showed that the efficiency of utilization of amino acid decreased with maturity and, conversely, there was a proportional increase of the requirement per kg of weight gain. The procedure based on the Gompertz function to determine the efficiency of utilization of amino acid proved to be suitable to evaluate the efficiency of utilization of amino acid and can be a useful tool to diagnose the effectiveness of the nutritional management, aiding in decision-making on the nutritional management.

O objetivo deste estudo foi desenvolver um procedimento baseado na função Gompertz para determinar a eficiência de utilização do aminoácido. O procedimento foi aplicado para determinar a eficiência de utilização da lisina, metionina+cistina e treonina da dieta de frangas de postura em crescimento, e com base nas eficiências foram estimadas as exigências para fase de crescimento das aves. A função Gompertz foi ajustada aos dados de consumo de ração, peso corporal, peso proteico do corpo depenado e peso de penas de quatro linhagens de aves de postura na fase de crescimento. As taxas de consumo e deposição diária de proteína (DP) foram calculadas. A deposição do aminoácido foi obtida multiplicando a DP pela concentração do aminoácido nas penas e corpo depenado. Os resultados obtidos demonstraram que as eficiências de utilização dos aminoácidos diminuíram com a maturidade e, inversamente, houve um aumento proporcional da exigência por kg de ganho de peso. O procedimento baseado na função Gompertz para determinar a eficiência de utilização do aminoácido mostrou ser adequado para avaliar a eficiência de utilização do aminoácido e pode ser uma ferramenta útil para diagnosticar a eficácia do manejo nutricional auxiliando na tomada de decisões sobre o manejo nutricional.
Um procedimento para avaliar a eficiência de utilização do aminoácido dietético para aves
Keywords: curva de crescimento; lisina; metionina+cistina; peso proteico; frangas; treonina; growth curve; lysine; methionine+cystine; protein weight; pullets; threonine